G-strand binding protein 2 is involved in asexual and sexual development of Plasmodium berghei. (June 2020) - Niikura, Mamoru; Fukutomi, Toshiyuki; Fukui, Kana; Inoue, Shin-Ichi; Asahi, Hiroko; Kobayashi, Fumie
Abstract: G-strand binding protein 2 (GBP2) is a Ser/Arg-rich (SR) protein involved in mRNA surveillance and nuclear mRNA quality control in yeast. However, the roles of GBP2 in virulence and sexual development in Plasmodium parasites are unclear, although GBP2 is involved in the asexual development of Plasmodium berghei, the rodent malaria parasite . In this study, we investigated the role of GBP2 in virulence and sexual development of P. berghei using gbp2 -deleted P. berghei (Δ gbp2 parasites). Then, to identify factors affected by gbp2 deletion, we performed a comparative proteomic analysis of the Δ gbp2 parasites. We found that GBP2 was not associated with the development of experimental cerebral malaria during infection with P. berghei, but asexual development of the parasite was delayed with deletion of gbp2 . However, the development of P. berghei gametocytes was significantly reduced with deletion of gbp2 . Comparative proteomic analysis revealed that the levels of adenosine deaminase (ADA), purine nucleoside phosphorylase (PNP), and hypoxanthine-guanine phosphoribosyltransferase (HGPRT) in Δ gbp2 parasites were significantly higher than those in wild-type (WT) parasites, suggesting that biosynthesis of purine nucleotides may be involved in function of GBP2. Therefore, we investigated the effect of purine starvation on the sexual development and proteome. In nt1 -deleted P. berghei (Δ nt1 parasites), the production of male and female gametocytes was significantly reduced compared to that in WT parasites. Moreover, we found that protein levels of GBP2 in Δ nt1 parasites were markedly lower than in WT parasites. These findings suggest that GBP2 is primarily involved in the sexual development of malaria parasites, and its function may be suppressed by purine starvation. Graphical abstract: Unlabelled Image Highlights: GBP2 is not essential for the survival of the asexual blood stage of P. berghei ANKA. The development of experimental cerebral malaria is not affected by deletion of gbp2 . Production of gametocytes of P. berghei ANKA is reduced by deletion of gbp2 .